1984
DOI: 10.1007/bf02088650
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and correlates of bulimic behavior in a female high school population

Abstract: To investigate the incidence and correlates of bulimic behavior, 1268 high school females were surveyed. A 47-item questionnaire was used to identify a group of students that would meet the DSM-III criteria for a probable diagnosis of bulimia. Students were then compared across the four content areas of demographics; body perception and weight information; dieting, exercise and menstrual behavior; and frequency of bingeing and purging behavior. Results indicated that 4.9% of the students met rigorous criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
2
1

Year Published

1985
1985
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 22 publications
3
59
2
1
Order By: Relevance
“…Johnson, Lewis, Love, Lewis, and Stuckey (1984) found, for example, that 21% of their sample of female high school girls reported weekly or more frequent episodes of binge eating. But Gormally et al's (1982) BES was used Note.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson, Lewis, Love, Lewis, and Stuckey (1984) found, for example, that 21% of their sample of female high school girls reported weekly or more frequent episodes of binge eating. But Gormally et al's (1982) BES was used Note.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade we have seen a significant increase in the incidence of bulimia nervosa (Pyle, Mitchell, Eckert, & Halvorson, 1983;Johnson, Lewis, Love, Lewis, & Stuckey, 1984;. The symptom profile of these patients has been refined in the psychiatric literature such that the disorder can be diagnosed with increasing specificity (APA, 1980;.…”
mentioning
confidence: 99%
“…Halmi, Falk, and Schwartz (1981) reported that 4.2% of a series of 355 college students (59.8% of whom were women) reported that they had used diuretics, and 0.6% reported using them once a week or more often. Johnson, Lewis, Love, Stuckey, and Lewis (1984), in their study of 1268 high school students, reported that 4% reported using diuretics; 2.1% monthly, 0.7% weekly, and 1.2% on a daily basis. The precise reason for the diuretic use or misuse in these series was not clear.…”
Section: Diuretic Abuse In Bulimiamentioning
confidence: 99%